The Attenuated Protective Effect of Outer Membrane Vesicles Produced by a mcr-1 Positive Strain on Colistin Sensitive Escherichia coli - Li, Xue; Sun, Lang; Li, Congran; Yang, Xinyi; Wang, Xiukun; Hu, Xinxin; Nie, Tongying; Zhang, Youwen; You, Xuefu (Frontiers in Cellular and Infection Microbiology, 2021)
Resistance to colistin, especially mobilized colistin resistance (mcr), is a serious threat to public health since it may catalyze a return of the “pre-antibiotic era”. Outer membrane vesicles (OMVs) play a role in antibiotic resistance in various ways. Currently, how OMVs participate in mcr-1-mediated colistin resistance has not been established. In this study, we showed that both OMVs from the mcr-1 negative and positive Escherichia coli (E. coli) strains conferred dose-dependent protection from colistin. However, OMVs from the mcr-1 positive strain conferred attenuated protection when compared to the OMVs of a mcr-1 negative strain at the same concentration. The attenuated protective effect of OMVs was related to the reduced ability to absorb colistin from the environment, thus promoting the killing of colistin sensitive E. coli strains. Lipid A modified with phosphoethanolamine was presented in the OMVs of the mcr-1 positive E. coli strain and resulted in decreased affinity to colistin and less protection. Meanwhile, E. coli strain carrying the mcr-1 gene packed more unmodified lipid A in OMVs and kept more phosphoethanolamine modified lipid A in the bacterial cells. Our study provides a first glimpse of the role of OMVs in mcr-1 -mediated colistin resistance.